Interest in Table Tennis in Junior High School Students in Pinrang Regency - Suyudi, Imam (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
The purpose of this study was to determine the interest in table tennis among junior high school students in Pinrang Regency. The type of research conducted is a survey. The population used is junior high school students in Pinrang Regency. The samples used were 50 students of SMP Negeri 1 Pinrang, 50 students of SMP Negeri 4 Pinrang, and 50 students of SMP Negeri 5 Pinrang, in total the sample amounted to 50 students. Data collection technique using a questionnaire with the Likert system. The data analysis technique used is a descriptive percentage. The results of the study can be concluded that: (1) The interest in table tennis in students at SMP Negeri 1 Pinrang Regency is very low; (2) Interest in table tennis in students at SMP Negeri 4 Pinrang Regency is very low, (3) Interest in table tennis in students at SMP Negeri 1 Pinrang Regency is low; and (4) Overall, the interest in table tennis among students in Pinrang Regency Public Junior High School is very low.